2017
DOI: 10.1590/s1678-9946201759060
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition behavior of Haemagogus leucocelaenus (Diptera: culicidae), a vector of wild yellow fever in Brazil

Abstract: Haemagogus leucocelaenus, which is considered a major vector of wild yellow fever, exhibits acrodendrophilic habits and mainly deposits its eggs in treeholes and bamboo internodes. The selection of nursery sites is essential in the life history and reproductive success of mosquitoes. The present work investigated the preferred oviposition height and period of Hg. leucocelaenus in an Atlantic forest area in Rio de Janeiro. Sampling was performed using oviposition traps that were placed on plant material at 0, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…leucocelaenus made simultaneously in three Atlantic Forest sites, in 2015-2016, that is, before the arrival of the YFV epizootic wave in this part of southeast Brazil, curiously revealed distinct dynamics from the aforementioned pattern. Accordingly, in PNMNI and Jacarapaguá (~ 20 km away), (45) unexpected peaks were respectively recorded in August 2015 and October 2015, in the dry-cold season, while in Casimiro de Abreu (~ 130 km from PNMNI) (41) the egg counting peaked in December 2015, in the rainy summer as expected. Thus, variations in the population dynamics of Hg.…”
Section: Discussionsupporting
confidence: 66%
“…leucocelaenus made simultaneously in three Atlantic Forest sites, in 2015-2016, that is, before the arrival of the YFV epizootic wave in this part of southeast Brazil, curiously revealed distinct dynamics from the aforementioned pattern. Accordingly, in PNMNI and Jacarapaguá (~ 20 km away), (45) unexpected peaks were respectively recorded in August 2015 and October 2015, in the dry-cold season, while in Casimiro de Abreu (~ 130 km from PNMNI) (41) the egg counting peaked in December 2015, in the rainy summer as expected. Thus, variations in the population dynamics of Hg.…”
Section: Discussionsupporting
confidence: 66%
“…In addition to the moisture of the breeding site, the number of immersions that Hg . leucocelaenus eggs undergo during embryogenesis seems to be an important factor in hatching rates [ 7 ]. Thus, rainy and hot periods offer greater possibilities for multiple immersions of eggs.…”
Section: Discussionmentioning
confidence: 99%
“…According to Alencar et al [ 6 , 7 ], Hg . leucocelaenus is eclectic in terms of feeding habits and oviposition patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Tátila-Ferreira et al [ 48 ] suggested that the availability of resources is the leading indicator of the abundance of Hg. leucocelaenus in the different strata.…”
Section: Discussionmentioning
confidence: 99%
“…leucocelaenus in the different strata. Indeed, several authors consider the oviposition site as the main factor affecting the dispersal of female mosquitoes (e.g., Tátila-Ferreira et al [ 48 ]).…”
Section: Discussionmentioning
confidence: 99%